Measuring air-sea gas-exchange velocities in a large-scale annular wind-wave tank - Mesarchaki, Evridiki; Kräuter, Christine; Krall, Kerstin Ellen; Bopp, Maximilian; Helleis, Frank; Williams, Jonathan M. J.; Jähne, Bernd (Ocean science, 2015)
Abstract. In this study we present gas-exchange measurements conducted in a large-scale wind-wave tank. Fourteen chemical species spanning a wide range of solubility (dimensionless solubility, α = 0.4 to 5470) and diffusivity (Schmidt number in water, Scw = 594 to 1194) were examined under various turbulent (u10 = 0.73 to 13.2 m s−1) conditions. Additional experiments were performed under different surfactant modulated (two different concentration levels of Triton X-100) surface states. This paper details the complete methodology, experimental procedure and instrumentation used to derive the total transfer velocity for all examined tracers. The results presented here demonstrate the efficacy of the proposed method, and the derived gas-exchange velocities are shown to be comparable to previous investigations. The gas transfer behaviour is exemplified by contrasting two species at the two solubility extremes, namely nitrous oxide (N2O) and methanol (CH3OH). Interestingly, a strong transfer velocity reduction (up to a factor of 3) was observed for the relatively insoluble N2O under a surfactant covered water surface. In contrast, the surfactant effect for CH3OH, the high solubility tracer, was significantly weaker.
Gesehen am 29.05.2020